The Influence of Entrepreneurial Leadership, Entrepreneurship Competence on Sustainable Organizational Performance : The Mediation Role of Innovation Capability in MSME - Rifki Jundulloh; Yasmine Nasution (Tazkia Islamic Finance and Business Review, 2024)
This research analyze the influence of entrepreneurial leadership and entrepreneurial competence on sustainable organizational performance in Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with innovation capability as a mediating variable. This study is based on the important role of MSMEs in the Indonesian economy growth, but many MSMEs have difficulty maintaining business sustainability, especially green MSMEs. This study aims to understand the factors that can improve sustainability performance that not only prioritize economic performance but must consider social performance and environmental performance, especially in the context of tight competition and increasing environmental awareness. The methodology used is a quantitative approach with a sample of 119 respondents from green MSME managers in Indonesia. This study uses Structural Equation Model (SEM) analysis, with the results of the research showing that entrepreneurial leadership and entrepreneurship competence have a positive effect on innovation capability, which ultimately has an impact on sustainable organizational performance. Innovation capability is proven to play a significant mediating role in the relationship between entrepreneurial leadership, entrepreneurship competence, and sustainable organizational performance. These findings are expected to help stakeholders in MSMEs to adopt innovative and green entrepreneurial leadership styles in order to achieve better desires of the green MSME sector in Indonesia. Keywords: entrepreneurial leadership, entrepreneurship competence, innovation capability, sustainable organizational performance, green MSMEs